Recovery of anaerobic ammonium oxidation via hydrazine following sulfate inhibition. Issue 7 (27th May 2022) - Zhou, Shiqi; Chen, Zhi; Wang, Jin; Yue, Zhengbo
Abstract : The presence of sulfate in sewage treatment has obvious impacts on biological nitrogen removal. Abstract : The presence of sulfate in sewage treatment has obvious impacts on biological nitrogen removal. We explored the influence mechanism of sulfate on anammox and the recovery via hydrazine of anammox after inhibition. The sulfate inhibited HDH activity and functional gene abundance, which had serious effects on the metabolic process of hydrazine synthesis and oxidation. The conversion rates of ammonia nitrogen and nitrite dropped from 0.49 mgN gvss −1 h −1 and 0.63 mgN gvss −1 h −1 to 0.17 mgN gvss −1 h −1 and 0.25 mgN gvss −1 h −1 . The absolute abundance of hzs A, hzs B and hzo dropped greatly from 7.3 × 10 4 to 3.7 × 10 4, 17.5 × 10 5 to 4.9 × 10 4 and 1.8 × 10 4 to 0.35 × 10 4, respectively. After supplying 10 mg L −1 of hydrazine, the normal metabolism of anammox was maintained. The addition of hydrazine helps cells resist the decaying effects and enhances the recovery capability of anammox bacteria following inhibition. These results demonstrate the promise of recovering anammox activity via hydrazine.